2017
DOI: 10.1007/s11684-017-0532-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of prognosis after acute kidney injury in hospitalized patients

Abstract: The risk factors, especially laboratory indicators, of prognosis after acute kidney injury (AKI) remain unclear. We conducted a retrospective survey of Chinese People's Liberation Army General Hospital from January 1, 2012 to December 31, 2012 according to the AKI diagnosis standard issued by Kidney Disease Improving Global Outcomes. The epidemiological features and factors influencing hospital mortality and renal function recovery were evaluated through logistic regression analysis. Among 77 662 cases of hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…[ 36 ] Thrombocytopenia has also been associated with AKI and mortality in non-surgical settings. [ 37 , 38 ] Nonetheless, thrombocytopenia is also a marker for critically ill patients and may reflect an underlying disease. [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] Thrombocytopenia has also been associated with AKI and mortality in non-surgical settings. [ 37 , 38 ] Nonetheless, thrombocytopenia is also a marker for critically ill patients and may reflect an underlying disease. [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…hypoalbuminemia was found to be the major risk coefficient that affected the prognosis of older patients with AKI (80–100 years old) undergoing continuous renal replacement therapy (CRRT), and was related to the turnover of these patients.These results showed that malnutrition is one of the main causes of death and albumin is a predictor for the mortality of critically ill older patients with AKI. In the study of Nie et al15 it was found that albumin, BMI, total blood count of white blood cell, and total blood count of platelets were the predictors of mortality of AKI patients. Albumin belongs to the biomarkers of malnutrition and total blood count of white blood cell is a biomarker of inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…Patient comorbidities such as diabetes mellitus, hypertension, cardiovascular disease, chronic liver disease, and chronic obstructive pulmonary disease have also been identified as important AKI predictors [ 11 , 13 , 36 , 37 , 40 , 45 , 46 ]. Given the increasing incidence of HIV-infected patients in past few decades, HIV infection is also a risk factor that predisposes patients to AKI [ 47 , 48 ].…”
Section: Risk Factors For Akimentioning
confidence: 99%